Assessment the level of Urinary podocalyxin as an early biomarker in Diabetic Nephropathy - Yassin, Kanaan Faisal; A Zbaar, Sami (Journal of Neonatal Surgery, 2025)
Background: For a long time, measuring urinary albumin and glomerular filtration rate (GFR) was considered the key to diagnosing kidney disease. Due to the lack of early diagnosis, the search for new markers that can provide early diagnosis and avoid complications has become increasingly important. Podocyte cell injury or dysfunction plays an important role in the development and progression of many kidney diseases . This enhances the potential of using podocyte cell product targets specially in urine as useful clinical indicators for the diagnosis and monitoring of kidney diseases. Methods: A cross-sectional study will be carried out to a group of 70 diabetic patients with diabetic nephropathy 20 healthy control. A total of 25 mL urine was collected. Alb/Cr ratio in a random urine sample . Serum creatinine, serum albumin and HbA1C. Urinary Albumin / creatinine ratio. Urinary podocalyxin, nephrin and podocin were determined by using commercially available ELISA test. Results: the study revealed that patients with normoalbuminuria have higher urinary PCX. Level than healthy control group as well as revealed that 50% of patients with normoalbuminuria have higher urine podocalyxin levels. These findings suggest that in the early stages of kidney damage urinary podocalyxin first appears in the urine preceding microalbumin. The results obtained showed that urinary podocalyxin level was significantly increased in both UM/CR and CKD staging subgroups compared with the healthy control group. A gradual increase in urinary podocalyxin level with CKD stage, especially in 2 and 3 stages, and the higher sensitivity of urinary podocalyxin as compared to UM/CR ratio in early detection of kidney damage was demonstrated. Conclusions: Diabetes patients had much greater amounts of podocalyxin, nephrin, and podocin in their urine compared to the healthy control group.